The manufacture and performance of diodes made in dielectrically isolated silicon substrates containing buried metallic layers - Goh, Wang Ling (2009)
Results are reported on the performance of diffused p+n diode structures manufactured on a novel silicon-on-metalon-insulator (SMI) substrate. This substrate consists of a thin single crystal silicon layer on top of a tungsten disilicide covered oxidized silicon wafer. The diodes show excellent characteristics with an exponential current–voltage (I V ) relationship over nine orders of magnitude and an ideality factor of 1.005, under forward bias conditions. The reverse leakage current is low with a minority carrier lifetime of typically 500 µs. The diodes show no evidence of stress induced defects or degraded performance due to W migration during processing. The SMI substrate is therefore shown to be compatible with standard manufacturing processes.